Activities for the differentiated classroom - Gregory, Gayle (Thousand Oaks, Calif : Corwin Press Classroom, 2008)
Correlated to national academic standards, offers activities to supplement differentiated lessons in mathematics, science, social studies, language arts, physical education, art, and music. These ready-to-use tasks can be immediately incorporated into lesson plans, and each activity features objectives, materials lists, helpful tips on conducting the activity, and reproducibles.
Faculty
Keywords: Education, Elementary -- Activity programs; English language -- Study and teaching (Primary) -- Activity programs; Mathematics -- Study and teaching (Primary) -- Activity programs